STRATEGI ADAPTIF GURU DALAM PEMBELAJARAN PPKN BAGI SISWA DENGAN HAMBATAN FISIK DAN MOTORIK DI SEKOLAH DASAR INKLUSI - Kholifatul Novita Ningsih; Neddyana Pahlawaty; Prince Clinton Immanuel Chirstian Damanik; Hendriano Meggy (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to describe teachers’ strategies in implementing Civics Education (PPKn) learning for students with physical and motor impairments in inclusive elementary schools. The research was motivated by the challenges teachers face in creating fair and participatory learning for all students, particularly those with limited physical abilities who often experience barriers in mobility, accessibility, and classroom participation. A descriptive qualitative approach was employed, using in-depth interviews, classroom observations, and document analysis with five Civics teachers from three inclusive elementary schools in East Jakarta. The findings revealed that teachers adopted adaptive strategies through the modification of lesson plans, the use of visual and digital media, and the application of participatory methods involving peer buddies. The main challenges identified were limited school facilities, time constraints, and insufficient inclusive pedagogy training. These issues were addressed through collaboration among classroom teachers, special education teachers, and school principals. The study concludes that strong collaboration within the school community is essential to achieving inclusive PPKn learning, as it fosters empathy, tolerance, and appreciation for diversity. Effective strategies in inclusive Civics Education must emphasize adaptation, collaboration, and humanization as tangible manifestations of Pancasila values in the classroom.